Pendidikan Fiqih Berbasis Kompetensi - Munawir Sazali (LPPM IAIN Sorong, 2016)
Competence is a combination of knowledge, skills, values and attitudes are reflected in the habit of thinking and acting. Such competence can be applied in Fiqh Education. Jurisprudence education includes knowledge, skills and attitudes. Fiqh Education is to know the Islamic law (cognitive), comply with Islamic law (Affective) and implement Islamic law (psychomotor). Fiqh teachers not only give an example, but becomes model. Giving examples and practice means just in front of the class made up. An example means demonstrating good attitude naturally inside and outside the classroom. In this regard, fiqh education is based on understanding aspects. Thus yafqahu activity (understand) is activity of the heart, not just a reason activities, as in al-Qur`an. Whereas in the context of madrasah curriculum, education of fiqh, which is part of the subject of Islamic Education (PAI) is directed to prepare learners to know, understand, appreciate and practice the Islamic law which later became the basis of his outlook on life through counseling, teaching, practice and the use of experience. Thus, fiqh education not only introduces students to law of thing, but also equips skills to implement the law and encourages students to obey the law.